New variants and genotype-phenotype correlation of PPP3CA-related developmental and epileptic encephalopathy - Wang, Ting; Ouyang, Shijia; Niu, Xueyang; Cheng, Miaomiao; Yang, Ying; Yang, Yonghua; Tan, Quanzhen; Liu, Wenwei; Yang, Xiaoling; Zhang, Yuehua (Frontiers in Neuroscience, 2025)
ObjectiveTo explore the genotypic spectrum and refine the genotype-phenotype correlation of PPP3CA-related developmental and epileptic encephalopathy (DEE).Methodswhole-exome sequencing or whole-genome sequencing was performed to all patients. Clinical data of 15 epilepsy patients in current study and 21 epilepsy patients from published studies were collected and analyzed.ResultsIn this study, 15 patients were identified with 13 de novo PPP3CA variants. Among these, seven frameshift variants and one gene inversion between intron 11 and intron 13 (including exons 12 and 13) were novel. 80% of patients experiencing seizure onset before the age of one. The seizure types observed included epileptic spasms (93.3%), tonic seizures (46.7%), myoclonic seizures (46.7%), focal seizures (40.0%), atypical absence seizures (13.3%), generalized tonic-clonic seizures (6.7%) and myoclonic atonic seizures (6.7%). All patients exhibited global developmental delay. MRI abnormalities were noticed in 9 patients, including widened subarachnoid space, bilateral ventricular width, poor myelination of white matter, and dysplasia of the corpus callosum. 80% specifically diagnosed with infantile epileptic spasms syndrome (IESS). When combining data from this study and published studies, 66.7% of patients experienced seizure onset before the age of one, and 77.8% were diagnosed with IESS. In patients with variants located in the catalytic domain (CD), 45.4% patients exhibited multiple seizure types, while 45.4% patients presented only with epileptic spasms. In contrast, among patients with variants in regulatory domain (RD), 87% had multiple seizure types and only 8.7% had epileptic spasms alone. Additionally, 45.5% of patients with CD variants had comorbid autism spectrum disorders, compared to 13% patients with RD variants. Recurrent variants included p.His92Arg, p.Asp234Glu, p.Glu282Lys, and p.Ser419Asnfs*31.ConclusionThis study is the first to report a gene inversion in PPP3CA-related DEE. Patients with only epileptic spasms were more prevalent in those with CD variants, compared to those with RD variants. Conversely, patients with multiple seizure types were more common among those with RD variants. The most frequently diagnosed epileptic syndrome was IESS. Additionally, comorbid ASD were more commonly observed in patients with CD variants than in those with RD variants.